2021
DOI: 10.3390/molecules26051205
|View full text |Cite
|
Sign up to set email alerts
|

Quinoline Functionalized Schiff Base Silver (I) Complexes: Interactions with Biomolecules and In Vitro Cytotoxicity, Antioxidant and Antimicrobial Activities

Abstract: A series of fifteen silver (I) quinoline complexes Q1–Q15 have been synthesized and studied for their biological activities. Q1–Q15 were synthesized from the reactions of quinolinyl Schiff base derivatives L1–L5 (obtained by condensing 2-quinolinecarboxaldehyde with various aniline derivatives) with AgNO3, AgClO4 and AgCF3SO3. Q1–Q15 were characterized by various spectroscopic techniques and the structures of [Ag(L1)2]NO3Q1, [Ag(L1)2]ClO4Q6, [Ag(L2)2]ClO4Q7, [Ag(L2)2]CF3SO3Q12 and [Ag(L4)2]CF3SO3Q14 were unequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 106 publications
0
31
0
Order By: Relevance
“…A slightly modified procedure from our group was also used [22,23] in the synthesis of the Ag(I) complexes as shown in Scheme 2a,b.…”
Section: Synthesis Of Pyridinyl and Quinolinyl Ag(i) Complexesmentioning
confidence: 99%
“…A slightly modified procedure from our group was also used [22,23] in the synthesis of the Ag(I) complexes as shown in Scheme 2a,b.…”
Section: Synthesis Of Pyridinyl and Quinolinyl Ag(i) Complexesmentioning
confidence: 99%
“…Many scientific reports revealed that natural and synthetic quinolines are drawn considerable attention in medicinal chemistry [ 7 , 8 ]. The great attention paid by researchers to the study of quinoline derivatives is explained by their broad range of biological activities, such as anti-Alzheimer [ 9 ], antidiabetic [ 10 ], anti-inflammatory [ 11 ], antituberculosis [ 12 ], anticancer [ 13 ], antioxidant [ 14 ], and as inhibitors of SARS‐CoV‐2 (COVID-19) virus [ 15 – 17 ]. Therefore, compounds containing thiazole heterocycles are well known in medicinal chemistry [ 18 ], thiazole derivatives exhibit significant biological activities, such as antimicrobial and antimalarial [ 19 ], Alzheimer [ 20 ], antiproliferative agents [ 21 ], anticancer agents [ 22 ], and anti-inflammatory [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, there has been greater interest in the possibility of using metal ions such as Ag(I), Au(I) or Pt(II) in medicine [ 27 , 28 ]. Additionally, complexes of these metals with Schiff’s bases show interesting biological properties [ 29 , 30 , 31 , 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%